The influence of whole sonicated Pseudomonas aeruginosa antigens on experimental p. aeruginosa arthritis in rabbits: Ahmed Q. Al-Awadi@ and Mohammed J. Alwan - Al-Awadi, Ahmed Q. (The Iraqi Journal of Veterinary Medicine, 2014)
To study the influence of whole sonicated Pseudomonas aeruginosa antigens (WSPAgs) on experimental arthritis induced by this bacteria, 15 rabbits were divided into 3 equal groups. The 1st group was inoculated intraarticular with 0.2 ml of p. aeruginosa suspension (2×108 cfu/ml), the 2nd group was immunized with WSP Ags, and inoculated intraarticular as in the 1st group. The 3rd group was served as negative control group. At 30 day post inoculation the immunized (2nd) group showed increase in the cellular (DTH and IFN-γ) and humeral (IgG) immunity and moderate bacterial isolation from joints, blood and internal organs comparing with other groups. The 1st group showed sever symptoms and inflammatory reaction as well as very obvious gross and microscopical lesions in their joints including supportive reaction, pyogranulomatous lesions, necrosis, pannus reaction and destruction of the articular cartilage and the lesion extended to the subchondral bone leading to osteomyelitis, the 2nd group (immunized group) expressed mild to moderate inflammatory reaction and the microscopic examination indicate that the lesion was confined in the articular capsule. In conclusion the whole Pseudononas aeruginosa sonicated Ags (WSPAgs) protect the joint from the experimental infection by P. aeruginosa in a rabbit model.